Advanced sustainable carbon material from babassu biomass and its adsorption performance. (May 2023) - da Silva Lima, Paloma Nayra; Ghosh, Anupama; Nascimento, Ariane; Sousa Vieira, Laís Helena; Costa, Rubens Silva; Ferreira, Odair Pastor; Abreu, Guilherme J.P.; Fujisawa, Kazunori; Silva-Filho, Edson Cavalcanti; Gomes de Souza Filho, Antônio; Lobo, Anderson Oliveira; Terrones, Mauricio; et al.
Abstract: Activated carbon (AC) wasprepared from babassu mesocarp, an abundant biomass inBrazil. Thermal pretreatments, including hydrothermal carbonization and pyrolysis at different temperatures were applied along with potassium hydroxide activation, in synthesizing ACs with varying structure, electronic and surface properties. A thorough characterization of the ACs revealed their low structural order and high specific surface area, containing micropores and mesopores. Furthermore, negatively charged surface oxygen functional groups make them potential candidates as adsorbents for cationic chemical species. A detailed study of adsorption of methylene blue cationic dye was carried out by varying time, initial concentration, pH and ionic strength of the dye solution, which showed that the chief driving force of this adsorption is the Coulombic interaction on the surface, followed by diffusion throughout the pores. These ACsshowed fast and efficient dye uptake – the best sample showedequilibrium adsorption capacity of 388 mg g −1 for methylene blueand 220 mg g −1 for another cationic dye crystal violetduring 6 h –and thereby can be used as renewable and sustainable adsorbents. Graphical abstract: Image 1 Highlights: Brazilian babassu coconut biomass wasused to generate activated carbon (AC). Hydrothermal carbonization was used, following chemical activation with KOH. Methylene blue (MB) dye was used to examine the adsorption properties of AC. Efficient MB uptake was observed, owing to the active surface and porosity of AC. Synthesis parameters were varied to obtain the best possible adsorbent AC material.